Post Conflict Psycho-Social Dilemmas: : Experiences of Internally Displaced Persons from Ezza/Ezillo Communal Crisis - Emma-Echiegu, Nkechi; Eze, Ogbonnia; Izugbara, Chibuogwu; Mbam, Philip Ekene; Chigbo, Kenneth (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
This study aimed at exploring the psychological and social impacts of the Ezza-Ezillo communal crisis on lives of the victims who experienced the crisis. To achieve the objectives of the study, a qualitative research method was adopted. Participants comprised of persons who were internally displaced by the Ezza-Ezillo communal crisis. The sample comprised of 144 respondents aged between 10-80 years. The data was generated through in-depth interviews (IDIs) and focus group discussions (FGDs). Qualitative analysis revealed that the crisis created a sense of loss and emptiness in the lives of the crisis victims. Result also revealed that all the categories of the victims (children, youths and older people) were affected in different ways. It was further observed that the victims resorted to seeking solace in the religious worships, skills acquisition, petti trading, farming etc as part of their coping strategies. It was generally observed that the killings and displacements of family member shattered the hopes and aspirations of the victims of Ezza/Ezillo people, leaving them in a condition of psychological despair and social impotency. As findings further revealed, the crisis affected the victims’ ability to concentrate, find solutions to daily problems, and interact with others. We recommend that support of different kinds was very necessary and should be provided by individuals, organizations and government to help ameliorate the untold sufferings of the victims of Ezza-Ezillo communal crisis.